FREQUENCY OF SNORING AND SYMPTOMS OF SLEEP APNEA AMONG PAKISTANI MEDICAL STUDENTS - Pasha, Sara N.; Khan, Umar Ali (Journal of Ayub Medical College Abbottabad, 2003)
Background: Snoring and its related problem, sleep apnea, are very common. They occur in all ages and both sexes. Frequency varies in different communities therefore studies of other countries are invalid for Pakistan. The aim of this study is to assess the frequency of snoring and emergence of symptoms of sleep apnea among the affluent class young adult Pakistani population. Methods: Subjects were evaluated through a questionnaire. Questions pertained to quality of sleep, intensity and frequency of snoring and presence of symptoms such as waking up choking, morning headaches and morning dry mouth. Data were collected for age, sex, height and weight. Subjects were also asked if they took alcohol or any drugs. Results: A total of 111 subjects, M:F=2:3, age range between 18-23 years, responded to the survey. The frequency of snoring was 27% in males and 12% in females, with males admitting to snoring more night in the week than the females. 92% of both males and females graded their snoring as being softer than the sound of talking. 15% of the males and 38% of the females said they snored in every body position. Percentages of male and female snorers exhibiting symptoms of sleep apnea were very similar, with choking arousals at 6% and 5% respectively. Conclusion: This study was done on the young Pakistani population for the determination of frequency of snoring and the emergence of symptoms of sleep apnea. The results are similar to studies done on the adult population with snoring more common and louder among the males. Key Words: snoring, sleep apnea, prevalence, Pakistan, young adults.